U-Pb zircon age of quartz diorite from Ben Giang intrusive complex in the Ben Giang area, Quang Nam Province - Hieu, Pham Trung; Trung, Huynh (Vietnam Journal of Earth Sciences, 2015)
Ben Giang intrusive complex in the Ben Giang area, Quang Nam province, is one of the constituents of the Kon Tum Massif. It is composed of gabrodiorite, diorite, quartz diorite, granodiorite and granite. Rocks are primarily types of quartz diorite minerals include plagioclase 48 63%, quartz 20 33%, alkali feldspar 0 10%, hornblende 3-8%, biotite 5 15%. Zircons separated from a quartz diorite sample in the Ben Giang complex were chosen to determine the protolithic age for the complex. Twelve LA-ICP-MS U-Pb zircon analyses yielded concordant ages concentrated at 479 Ma (weighted mean). These results indicate the protolithic age of the quartz diorite (primary magma crystallization age) is Paleozoic (ca. 479 Ma). References A. Carter, D. Roque, C. Bristow, P. Kinny, 2001: Understanding Mesozoic accretion in Southeast Asia: Significance of Triassic thermotectonism (Indosinian orogeny) in Vietnam. Geology, 29 (3), 211-214. Nguyễn Thị Dung, Phạm Trung Hiếu, Nguyễn Trung Minh, 2015: Tuổi đồng vị U-Pb của zircon trong đá granitogneis phức hệ Đại Lộc và ý nghĩa địa chất của nó. Tc. Các khoa học về Trái Đất, T.37, 1, 28-35. Tran Trong Hoa, Tran Tuan Anh, Ngo Thi Phuong, Pham Thi Dung, Tran Viet Anh, Andrey E. Izokh, Alexander S. Borisenko, C.Y. Lan, S.L. Chung, C.H.Lo., 2008: Permo-Triassic intermediate-felsic magmatism of the Truong Son belt, eastern margin of Indochina. Comptes Rendus Geoscience, 340, 112-126. Phạm Trung Hiếu, Lê Thanh Mẽ, Vũ Lê Tú, Nguyễn Thị Bích Thủy, 2009: Tuổi đồng vị U-Pb zircon trong granit phức hệ Yê Yên Sun Tây Bắc Việt Nam và ý nghĩa của nó. Tc. Các Khoa học về Trái Đất, T.31, 1, 23-29. P.D. Kinny, J.R. Wijbrans, D.O. Froude, I.S.Williams and W. Compston., 1990: Age constraints on the geological evolution of the Narryer Gneiss Complex, Western Australia, Australia Journal of Earth Sciences, 37, 51-69. Nguyễn Quang Luật, Phạm Trung Hiếu, Nguyễn Tiến Thành, 2012. Tuổi U-Pb zircon và thành phần đồng vị Hf của gabrodiorit khối A-Bung, vùng Đăk Krông - A Lưới. Tạp chí Địa chất, A329, 19-29. E.A. Nagy, H. Maluski, C. Lepvrier, U. Scharer, P.T. Thi, A. Leyreloup and V.V. Tich, 2001: Geodynamic significance of the Kontum Massif in Central Vietnam: Composite 40Ar/39Ar and U-Pb ages from Paleozoic to Triassic, J. Geol., 109, 755-770. Tran Ngoc Nam, 1998: Thermotectonic events from early Proterozoic to Miocene in the Indochina craton: implication of K-Ar ages in Vietnam. J. Asian Earth Sci., 16, 475-484. Trần Ngọc Nam, 2004: Tuổi đồng vị U-Pb của zircon 436 triệu năm trong phức hệ Sông Re ở địa khối Kon Tum và ý nghĩa của nó, Tạp chí Địa chất, A281, 18-23. Trần Ngọc Nam, Y. Osanai, N. Nakano, Hoàng Hoa Thám, 2004: Biến chất nhiệt độ siêu cao Permi-Trias: Va chạm lục địa ở địa khối Kon Tum? TC Địa chất, A285, 1-8. Nguyen Kinh Quoc and Pham Duc Luong, 1986: The great stages of volcanic activities in Vietnam. Proc. 1st Conf. Geol. Indochina, 1: 179-190. Hanoi. Đào Đình Thục, Huỳnh Trung, 1995: Địa chất Việt Nam. Tập II. Magma. Cục Địa chất Việt Nam. Hà Nội, 359 tr. Trần Văn Trị, Vũ Khúc (chủ biên), 2009: Địa chất và Tài nguyên Việt Nam. Nxb. Khoa học Tự nhiên và Công nghệ, Hà Nội, 390tr. Huỳnh Trung, Nguyễn Xuân Bao, 1979: Về quy luật phân bố các thành tạo magma xâm nhập ở miền Nam Việt Nam. Địa chất và khoáng sản-công trình của Liên đoàn bản đồ Địa chất. Quyển 1, 111-136, Hà Nội. Huỳnh Trung, Trần Phú Hưng, Lê Đức Phúc, Trần Đại Thắng, Đinh Quang Sang, Bùi Thị Luận, Trịnh Nguyễn Hùng Vỹ, Trương Chí Cường, Phạm Quang Vinh, 2004: Các thành tạo magma xâm nhập phần phía Nam Việt Nam (từ Quảng Trị trở vào). Tuyển tập báo cáo Hội thảo khoa học nghiên cứu cơ bản trong lĩnh vực các KHTĐ. Đại học Quốc Gia Hồ Chí Minh, 3-35. T. Usuki, C. Y. Lan, T. F. Yui, 2009: Early Paleozoic medium-pressure metamorphism in central Vietnam: evidence from Shirmp U-Pb zircon ages. Geosciences Journal, 13(3): 245-256. Y. Wang, W. Fan, G. Zhao, S. Ji and T. Peng, 2007: Zircon U-Pb geochronnology of gneissic rocks in the Yunkai massif and ít implications on the Caledonian event in the South China Block. Gondwana Research, 12, 404-416. I.S. Williams and S. Claesson, 1987: Isotopic evidence for the Precambrian provenance and Caledonian metamorphism of high grade paragneisses from the Seve Nappes, Scandinavian Caledonides: II. Ion microprobe zircon U-Th-Pb: Contribution to Mineralogy and Petrology, 97, 205-217. X. H. Zhou, 2003: My thinking about granite genses of South China. Geological Journal of China Universityies, 9 (4): 556-565 (in Chinese with English abstract). C. L. Zhu, B. Long. 1997: Evolution of granitoids in Southern China. Geotectonica et Metallogenia, 21 (2): 181-188 (in Chinese). Nguyễn Văn Vượng, Vũ Văn Tích, Hansen Bent, 2004: Áp dụng phương pháp Tims U/Pb xác định tuổi kết tinh của khối Đại Lộc. Tc. Khoa học về Trái Đất, T.26, 3, 202-207.